Mapeamento do potencial de geração fotovoltaica: uma conquista sustentável - Morais, Paulo Roberto Ribeiro (2023)
The diversification of the electric matrix, through the use of renewable sources, has been stimulated in several countries around the world to reduce the use of fossil fuels, contributing to the fight against global warming. In Brazil, despite having an essentially renewable matrix, there is a strong dependence on the hydroelectric source. Therefore, it is important to increase the participation of other renewable sources in the national matrix. The such task starts by mapping the generation potential in the territory for other sources. Some studies have mapped the energy potential of renewable sources at the national and regional levels, however, these studies consider only one variable and are of a very wide geographic scale, which limits their applications at the municipal scale. This research aims to develop a methodology for mapping the potential of renewable energy generation, with a focus on photovoltaic generation, at a local scale. To this end, we conducted a systematic literature review, to analyze the mapping models used in science; we examined the Brazilian legislative environment, to understand how each federative entity can collaborate with the diversification of the matrix; and finally, we proposed a model to map the potential for photovoltaic energy generation and tested it in the municipality of Vitória da Conquista, Bahia. The systematic review revealed that the mapping of electric power generation potentials should be done using Multicriteria Decision Analysis techniques and, the most used is the Analytic Hierarchy Process. Furthermore, the lack of mapping studies of the generating potential at the local scale was evidenced. The analysis of the national legislative environment showed that there are few regulations in the Brazilian legal framework for energy production. Furthermore, due to the 1988 Federal Constitution, States and Municipalities cannot legislate directly on the subject, acting marginally in promoting the use of sustainable energy sources. Finally, the model for mapping the potential of photovoltaic energy, combined the methods of Analytic Hierarchy Process, Boolean analysis and Fuzzy modeling. In the model we propose, five classes of photovoltaic energy generation potential are generated: restricted areas, low, moderate, high, and excellent. The test performed in the city of Vitoria da Conquista revealed that the analyzed territory is promising for photovoltaic generation since 17.62% of the area composes the high or excellent classes. Considering only the area of the excellent class, annual production of electric energy between 15.9 GWh and 16.4 GWh was estimated. The method also has the potential to be applied in Brazilian municipalities because it uses generic variables and parameters that are not restricted to the test area.